PLANE: A Platform for Negotiation of Multiattribute Multimedia Objects - Guedes, Rharon M. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
This work proposes the definition of a system to negotiate products in an e-commerce scenario. This negotiation system is defined as PLANE – Platform to Assist Negotiation – and it is carried in a semi-automatic way, using multi-attributes functions, based on attributes of the negotiated content. It also presents an architecture to interconnect the participant through an inter-network in the television broadcasters context. Each participant of the inter-network applies policies for its own contents, and all of them must comply these policies. If a participant needs a content not covered by the policies, it is possible to start a negotiation process for this specific content. Experiments present a simulation scenario where PLANE assists the negotiation between three sellers and one buyer with predefined negotiation profiles. Results demonstrated the success of the system in approximate the negotiator after some few interactions, reducing time and cost.
Keywords: e-commerce; negotiation; inter-network; multi-attribute; multimedia; IJIMAI